The Tectonic Map and Structural Provinces of the Late Neoproterozoic Egyptian Nubian Shield: Implications for Crustal Growth of the Arabian–Nubian Shield (East African Orogen) - Hamimi, Zakaria; Hagag, Wael; Fritz, Harald; Baggazi, Haitham; Kamh, Samir (Frontiers in Earth Science, 2022)
The Late Neoproterozoic Egyptian Nubian Shield (ENS) has attracted increasing attention since the establishment of the Egyptian Geological Survey and Mining Authority; EGSMA (1896), which conducted the first mapping. In the last three decades, rapid improvements in analytical techniques, along with field-oriented studies, has made possible interpretation of ENS as an integral part of the juvenile Arabian-Nubian Shield (ANS) as portion of the East African Orogen (EAO). However, a consistent tectonic map of the ENS doesn’t exist. Presentation of such a map is the main objective of the present work where Landsat-based lithological discrimination is combined with systematic structural investigation and careful reassessment of previously published geological maps. Our interpretation of this map indicates that in accordance with a previous work, the basement units of the Eastern Desert (ED) can be divided into three structural domains; Northern, Central and South Eastern Deserts provinces. The proposed provinces are ascribed to three different plate tectonic far-field boundary conditions. The earliest magmatic, metamorphic and tectonic history was set off by the approximate north-south convergence of the Gabgaba - Gebeit, Jiddah – Asir terranes and Eastern Desert-Midyan terranes along the Yanbo-Onib-Sol-Hamid-Gerf-Allaqi-Heiani (YOSHGAH) suture between c. 800 and 620 Ma. The second event between c. 640 and 580 Ma was correlated with the Nabitah Orogeny when the Ad Dawadimi-Ar Rayn terranes in the eastern Arabian Shield accreted to the earlier consolidated arc terranes (Afif and Tathlith terranes). During this period, east-west convergence between northwestern Saudi Arabia and Central Eastern Desert (CED) in Egypt caused a pronounced strike-slip deformation associated with the displacement along the wider Najd Fault system. The third orogenic phase, which was younger than c. 580 Ma, was controlled by the evolution and retreat of the Cadomian Arc. The northern portions of ENS and the northern Arabian Shield experienced extension whereas extensive post-orogenic magmatism was related to mantle delamination and associated crustal thinning.